2022
DOI: 10.1177/10783903221146190
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Nursing Workforce Survey: Results and Implications

Abstract: Objective: The last national survey of psychiatric-mental health (PMH) nurses was conducted in 2016 and was limited to advanced practice registered nurses (APRNs). Data on the demographic and employment characteristics of the PMH workforce could inform how to optimize the PMH nursing workforce to address increasing demands for mental health services. The objective was to conduct a national survey of PMH registered nurses (RNs) and PMH-APRNs to gather data on their demographic, educational, and practice charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…A review of related research indicates that the PMHN role is increasingly psychotherapeutic (Gerolamo et al ., 2022). The present study found that some nurses prioritized contact with patients, whereas others were unwilling to talk to them because they were concerned that they would not be able to manage any needs that emerged, and they did not have much time to do so.…”
Section: Discussionmentioning
confidence: 99%
“…A review of related research indicates that the PMHN role is increasingly psychotherapeutic (Gerolamo et al ., 2022). The present study found that some nurses prioritized contact with patients, whereas others were unwilling to talk to them because they were concerned that they would not be able to manage any needs that emerged, and they did not have much time to do so.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, racial/ethnic minority groups, rural communities, and sex and gender minority groups have disproportionately poor access to mental health care (Agency for Health care Research and Quality, 2022; Gerolamo et al, 2022; Mongelli et al, 2020; Reynish et al, 2021; Willging et al, 2006). A recent report by the Satcher Health Leadership Institute highlighted that between 2016 and 2020, among indigenous and racial/ethnic minoritized groups, there were 116,722 excess premature mental and behavioral health-related deaths, resulting in an excess of US$278 billion cost burden due to mental illness, substance use, and suicide (Dawes et al, 2022).…”
mentioning
confidence: 99%
“…We choose to practice among underserved populations and areas of poor care access, as well as lead scientific inquiry into innovative solutions to inequities in mental health care delivery and access (American Psychiatric Nurses Association, 2022; Myers, 2019). We further increase our visibility and accessibility as an indispensable part of the mental health workforce by deliberately providing care in diverse practice settings and leveraging novel technologies (such as tele-mental health; Gerolamo et al, 2022; Lattie et al, 2022; Myers, 2019; Talarico, 2021). Finally, we actively pursue opportunities to “sit at the table” and advocate for mental health parity by educating key stakeholders regarding who we are and what we do as important solutions to mental health care workforce shortages and inequitable provider distribution across the nation (Chapman et al, 2018; Hurley et al, 2022).…”
mentioning
confidence: 99%
“…As the second largest group of mental and behavioral health professionals in the United States, PMH nurses are an important solution to worker shortages. Improving access to mental health care is contingent upon eliminating system-level barriers to full utilization of our adequately trained and readily available PMH nursing workforce (Chapman et al, 2018) we leverage virtual platforms and novel technologies to deliver care, and we are readily available and willing to provide care for Medicaid recipients and other individuals from low-income and often marginalized communities (Gerolamo et al, 2022). When restrictions to our scope of practice that hinder us from practicing to the full extent of our education and training are removed, we are a veritable solution to the provider shortages.…”
mentioning
confidence: 99%
“…Improving access to mental health care is contingent upon eliminating system-level barriers to full utilization of our adequately trained and readily available PMH nursing workforce (Chapman et al, 2018). As highlighted by the Australian Primary Health Care Nurses Association (APNA) workforce report, PMH nurses practice across a wide variety of inpatient, outpatient, and private practices, we leverage virtual platforms and novel technologies to deliver care, and we are readily available and willing to provide care for Medicaid recipients and other individuals from low-income and often marginalized communities (Gerolamo et al, 2022). When restrictions to our scope of practice that hinder us from practicing to the full extent of our education and training are removed, we are a veritable solution to the provider shortages.…”
mentioning
confidence: 99%